A study on identifying patterns and characteristic of Checked Punca Potong Cloth (CPPC) weaving: a systematic review - Ahmad, Nani Hartina; Shaari, Nazlina; Mohd Ali, Nor Azizi; Abd Latif, Muhammad Pauzi (International Service Innovation Design Conference (ISIDC), 2018)
The beauty of Malay textile is derived from a combination of creative patterns, motifs and the value of gold within a community. All these factors determine its commercial and aesthetic value. This paper is aim to propose a new systematic review to identify the patterns and characteristic of Checked Punca Potong Cloth (CPPC). It is shown that the patterns and characteristic of weaving design can be used as a unified point of review and therefore shall be applied as the review method of CPPC for this research. The type of patterns is briefly introduced; while certain matters relating to the review of this identification method are discussed, including search strategy and selection criteria of patterns and characteristic in weaving design. The result shows that the specific checked design studies it can be more to improve for the future research in order to increase representativeness and generalization of data.